2008
DOI: 10.1016/j.bbr.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine D1 and D2 receptors in the nucleus accumbens shell on the acquisition and expression of fructose-conditioned flavor–flavor preferences in rats

Abstract: Systemic administration of dopamine D1 (SCH23390) and less so D2 (raclopride) receptor antagonists significantly reduce acquisition and expression of fructoseconditioned flavor preferences (CFP). Because dopamine in the nucleus accumbens shell (NAcS) is implicated in food reward, the present study examined whether NAcS D1 or D2 antagonists altered acquisition and/or expression of fructose-CFP. In Experiment 1, food-restricted rats with bilateral NAcS cannulae were trained to drink a fructose (8%) + saccharin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 31 publications
8
58
2
1
Order By: Relevance
“…Analysis of central sites of action revealed that the acquisition of fructose-CFP was blocked by DA D1 or D2 antagonists in the mPFC and by DA D2 antagonists in the AMY. In contrast, expression of fructose-CFP was reduced by DA D1 or D2 antagonists in the NAcS or AMY, but not the mPFC (Bernal et al, 2008, 2009; Malkusz et al, 2012), and by DA D1 antagonism in the lateral hypothalamus (Amador et al, 2014). Thus, mPFC DA D1 and D2 receptor signaling in a frontal cortical projection zone of the VTA meso-cortical DA system was intimately involved in the acquisition or learning, but not the expression or maintenance of fructose-CFP.…”
Section: Discussionmentioning
confidence: 87%
“…Analysis of central sites of action revealed that the acquisition of fructose-CFP was blocked by DA D1 or D2 antagonists in the mPFC and by DA D2 antagonists in the AMY. In contrast, expression of fructose-CFP was reduced by DA D1 or D2 antagonists in the NAcS or AMY, but not the mPFC (Bernal et al, 2008, 2009; Malkusz et al, 2012), and by DA D1 antagonism in the lateral hypothalamus (Amador et al, 2014). Thus, mPFC DA D1 and D2 receptor signaling in a frontal cortical projection zone of the VTA meso-cortical DA system was intimately involved in the acquisition or learning, but not the expression or maintenance of fructose-CFP.…”
Section: Discussionmentioning
confidence: 87%
“…The dopamine reward system is also implicated in fructose-conditioned flavor preferences [2,5] and the differential sipper tube conditioning response to sucrose and non-nutritive sweeteners (sucralose, saccharin) [3,10]. Conceivably, fructose may activate the dopamine reward system more than does the highly preferred SS or equally preferred saccharin solutions used in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…of action revealed that acquisition, but not expression of IG glucose-CFP was blocked by a DA D1 antagonist administered into the nucleus accumbens, amygdala, medial prefrontal cortex and lateral hypothalamus (Touzani et al, , 2009a(Touzani et al, , 2009b(Touzani et al, , 2010, whereas a DA D1 antagonist administered into these same sites differentially reduced acquisition and expression of fructose-CFP (Amador et al, 2014;Bernal et al, 2008Bernal et al, , 2009Malkusz et al, 2012). In contrast, opioid receptor antagonism with naltrexone failed to affect the acquisition or expression of CFPs in rats produced by IG sucrose or orally-consumed fructose (Azzara et al, 2000;Baker et al, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 55%